Alleviative effect of short-clustered maltodextrin on the quality deterioration of frozen dough: Compared with trehalose and guar gum. (September 2021) - Li, Yang; Li, Caiming; Ban, Xiaofeng; Cheng, Li; Hong, Yan; Gu, Zhengbiao; Li, Zhaofeng
Abstract: The alleviative effect of short-clustered maltodextrin (SCMD) on the quality deterioration of frozen steamed bread dough was investigated in terms of bread characteristics and dough properties with different analytical methods. The results showed that after 56-day frozen storage, SCMD bread had a larger specific volume, lower hardness and looser, more uniform crumb structure compared with Control bread, trehalose (TH) bread and guar gum (GG) bread. Dough viscoelasticity analysis found that the elastic module (G′) of SCMD dough was significantly higher than TH dough but lower than that of GG dough. However, the magnitude of decrease in G′ of GG dough was considerably higher than that of SCMD dough through 56-day frozen storage, which indicated that SCMD could effectively alleviate the damage of long-term frozen storage to gluten. Besides, the gassing rate of SCMD dough, TH dough and GG dough decreased by 15.11%, 20.39% and 23.47% after 56-day frozen storage compared with their respective fresh dough, which indicated the addition of SCMD alleviated the decline of dough gassing rate more effectively. Through SEM analysis, the microstructure of dough after frozen storage was characterized. And the relationships among fractal dimension of bread slices, dough gassing rate and dough elastic module were established for the first time. Finally, analysis of the conformation model further confirmed the possibility of SCMD binding to ice surface by hydrogen-bond interaction, but the MD simulations on binding structures of SCMD-ice complexes need to be further explored. Graphical abstract: Image 1